Amino Acid–Substituted Dextran-Based Non-Viral Vectors for Gene Delivery - Zink, Matthias; Hotzel, Konrad; Schubert, Ulrich S.; Heinze, Thomas; Fischer, Dagmar (Macromolecular Bioscience, 2019)
To form bio-inspired non-viral vectors for DNA delivery, the polysaccharide dextran is allowed to react with Boc-amino protected amino acids glycine, β-alanine, and L-lysine activated with 1,1’-carbonyldiimidazole and subsequent dextran ester deprotection. A library of such dextran esters is made available to investigate the relationship between polymer structure, complex formation, stability, toxicity, and transfection. Only dextran esters of β-alanine and L-lysine are able to efficiently interact with DNA as shown by dye exclusion assays, to form nanosized complexes (70–110 nm) with positive zeta potential. With increasing substitution degree and complex charge ratios, the L-lysine esters accomplish more effective binding and protection of DNA against enzymatic degradation than β-alanine esters. However, luciferase reporter gene assays reveal higher transfection for β-alanine than for L-lysine esters due to a more effective DNA release and better suited buffing area of the amino groups triggering the endosomal release. Conclusively, β-alanine-substituted dextran derivatives may serve as promising non-viral vectors.
CRIS-Team Scopus Importer:2020-10-13
Keywords: amino acid; dextran ester; gene delivery; polysaccharides; transfection